Hydrolysis Patterns of Xylem Tissues of Hardwood Pretreated With Acetic Acid and Hydrogen Peroxide - Lee, Dae-Seok; Lee, Yoon-Gyo; Song, Younho; Cho, Eun-Jin; Bae, Hyeun-Jong (Frontiers in Energy Research, 2020)
The structural recalcitrance of lignocellulose limits its enzymatic hydrolysis, which leads to inefficient enzyme usage and inhibition of saccharification, depending on the pretreatment method. Research on the structural properties of xylem tissues of hardwood and their effect on enzymatic saccharification is necessary to achieve cost-effective biofuel production via improved enzyme cocktail preparation. Oak wood (Quercus acutissima) was pretreated and delignified with a hydrogen peroxide-acetic acid (HPAC) solution. Cellulose was found to undergo significant swelling in the lumen of the wood fiber, and it was sorted into readily hydrolysable (72.9%), mid-hydrolysable (8.2%), and hardly hydrolysable (18.9%) cellulose forms. Oak wood has been shown to be strongly retarded among the various types of hardwoods. The recalcitrance of the xylem tissues, such as wood fibers, tracheids, vessel elements, and ray parenchyma cells, was determined through analysis of the hydrolysis rates. It was found to increase in the following order: ray parenchyma cells < tracheids < wood fibers or vessel elements < tracheids < wood fibers. The wood fibers were almost enzymatically fragmented into pieces ~90 μm in length at crack sites in 6 h. The wood fibers were digested faster in the S3 or S2 wall than in the primary wall. The result indicated that the primary wall may be a structural retardation factor in the hardwood as sorted to the hardly hydrolysable cellulose. In presence of 10% substrate supplemented with enzymes to reduce the structural recalcitrance (xylanase and lytic polysaccharide monoxygenase) and end-product inhibitions (beta-glucosidase), the hydrolysis rate was increased by 55.21%. Ethanol fermentation exhibited a higher efficiency when a single substrate (Q. acutissima) rather than a mixture of various hardwoods was used. Of all the xylem tissues of hardwood that were delignified by HPAC pretreatment, wood fiber was found to be a structural retardation factor owing to the recalcitrance its primary wall. Thus, enzyme preparation can enable the rapid and efficient hydrolysis for the commercialization of bioethanol from hardwood.